Micro-Renovation Method of Old Residential Areas Based on Parametric Energy Simulation: An Aging Community in Middle China as an Example - Ziyun Ye; Shulin Ouyang; Xiong Gao; Yaming Ren (Buildings)
In the context of urbanization, the renewal of old communities constitutes a crucial aspect for enhancing the living environment. Currently, the social benefits and utilization efficiency achieved through the renewal of such neighborhoods fall short of meeting the demands of society, urban management, and residents. Existing research on old community renewal predominantly centers on environmental beautification and infrastructure augmentation or relies on diverse data for interpreting and analyzing the current state of these spaces while overlooking in-depth investigations into the design methodologies for public spaces within old communities. This paper presents a comprehensive strategy, termed “Demands–Design–Verify (DDV)”. This paper selected an old community in Changsha City (China) as a case study and used the following: (1) a questionnaire investigation and observation (Demands); (2) parameterized simulation data and UTCI energy data put forward for the optimization strategy of aging community public space (Design); (3) space syntax, physical environmental simulation data, and a one-way analysis of variance to validate the effectiveness of the design (Verify). The research results indicate that the public space renewal outcomes of old-aged communities under the guidance of this method have positive effects in aspects such as solar radiation, thermal comfort, spatial accessibility, and pedestrian flow. The method exhibits universality and ease of implementation for public space renewal in old communities, thus providing scientific methodological guidance for urban residential renewal.